Redescription and Natural History of the Mexican harvestman Diguetinus raptator Roewer, 1912 (Opiliones: Globipedidae), type species of the genus - Cokendolpher, James C.; Lucio-Palacio, Cesar Raziel; Staręga, Wojciech (Zootaxa, 2021)
The taxonomy of the monotypic genus Diguetinus Roewer, 1912 is discussed with a redescription of the only named species. The redescription, illustrations, and photographs are based upon male and female type specimens as well as a pair of more recently collected specimens from a relatively nearby location; both in Jalisco, Mexico. The genitalia are illustrated for the first time. A distribution map is provided with all verified records from iNaturalist included from: Aguascalientes, Jalisco, Guanajuato, Querétaro, Michoacán, Estado de México, Ciudad de México, Hidalgo, and Puebla. All available knowledge on the natural history is presented including biogeography and distribution, local distribution and habitat use, influence of physical factors, and interspecific relations.